Alexander the Great and his empire : a short introduction - Briant, Pierre (Book collections on Project MUSE., 2010)
This is the first publication in English of Pierre Briant's classic short history of Alexander the Great's conquest of the Persian empire, from the Mediterranean to Central Asia. Eschewing a conventional biographical focus, this is the only book in any language that sets the rise of Alexander's short-lived empire within the broad context of ancient Near Eastern history under Achaemenid Persian rule, as well as against Alexander's Macedonian background.